A genetic variant in proximity to the gene LYPLAL1 is associated with lower hunger feelings and increased weight loss following Roux-en-Y gastric bypass surgery. (1st September 2016) - Bandstein, Marcus; Mwinyi, Jessica; Ernst, Barbara; Thurnheer, Martin; Schultes, Bernd; Schiöth, Helgi B.
Abstract: Objective: Bariatric surgery is the most efficient treatment of severe obesity. We investigated to what extent BMI- or waist-hip ratio (WHR)-related genetic variants are associated with excess BMI loss (EBMIL) two years after Roux-en-Y gastric bypass (RYGB) surgery, and elucidated the affected biological pathways. Methods: Two-hundred fifty-one obese patients (age: 43 ± 10.7, preoperative BMI: 45.1 ± 6.1 kg/m 2, 186 women) underwent RYGB surgery and were followed up after two years with regard to BMI. Patients were genotyped for 32 single-nucleotide polymorphisms (SNPs) that were investigated with regard to their impact on response to RYGB and preoperatively measured Three Factor Eating Questionnaire (TFEQ) scores. Results: Homozygous T carriers of the SNP rs4846567 in proximity to the Lysophospholipase-like 1 ( LYPLAL1 ) gene showed a 7% higher EBMIL compared to wild-type and heterozygous carriers ( p  = 0.031). TT-allele carriers showed furthermore lower scores for Hunger (74%, p  < 0.001), lower Disinhibition (53%, p  < 0.001), and higher Cognitive restraint (21%, p  = 0.017) than GG/GT carriers in the TFEQ. Patients within the lowest quartile of Hunger scores had a 32% greater EBMIL compared to patients in the highest quartile ( p  < 0.001). Conclusion: The LYPLAL1 genotype is associated with differences in eating behavior and loss of extensive body weight following RYGB surgery. Genotyping and the use of eating behavior-related questionnaires may help to estimate the RYGB-associated therapy success.